2018
DOI: 10.1017/s1743923x18000168
|View full text |Cite
|
Sign up to set email alerts
|

(De)constructing the Masculine Blueprint: The Institutional and Discursive Consequences of Male Political Dominance

Abstract: Men are overrepresented in most legislatures of the world. However, in parliaments in which women reach a “critical mass” or even approach parity with men in terms of numbers, they still must contend with and adapt to the symbolic representation of men. Using the cases of the Australian and Polish parliaments, we point to the need to deconstruct the parliamentary standard by shifting the theoretical and empirical focus from women's disadvantage in politics to problematizing men's advantage and power (Eveline 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Gender inequality and sexism are often framed in terms of disadvantages for women. However, feminist scholars point out the importance of also acknowledging and dismantling male privileges to overcome sexism, patriarchal arrangements, and masculinist standards (Galea & Gaweda, 2018;Pease, 2010). Past research has shown, for example, that becoming aware of one's group-based privileges and perceiving them to be unjust is a central component in motivating political allyship against systems of inequality (Droogendyk et al, 2016;.…”
Section: Appraisal Of Male Privilegementioning
confidence: 99%
“…Gender inequality and sexism are often framed in terms of disadvantages for women. However, feminist scholars point out the importance of also acknowledging and dismantling male privileges to overcome sexism, patriarchal arrangements, and masculinist standards (Galea & Gaweda, 2018;Pease, 2010). Past research has shown, for example, that becoming aware of one's group-based privileges and perceiving them to be unjust is a central component in motivating political allyship against systems of inequality (Droogendyk et al, 2016;.…”
Section: Appraisal Of Male Privilegementioning
confidence: 99%
“…Gender inequality and sexism are often framed in terms of disadvantages for women. However, feminist scholars point out the importance of also acknowledging and dismantling male privileges to overcome sexism, patriarchal arrangements, and masculinist standards (Galea & Gaweda, 2018;Pease, 2010). Past research has shown, for example, that becoming aware of one's group-based privileges and perceiving them to be unjust is a central component in motivating political allyship against systems of inequality (Droogendyk et al, 2016;.…”
Section: Appraisal Of Male Privilegementioning
confidence: 99%
“…This paper deconstructs the partisan practices comprising the “masculine blueprint” (Galea and Gaweda 2018) of state legislatures that legitimizes the dominance of men in state legislatures. In so doing, this paper contributes to scholarship challenging the assumption that legislatures become less gendered as more women enter them (Funk et al.…”
Section: Parties Gender and Representationmentioning
confidence: 99%